Unsaturated or saturated dietary fat-mediated steatosis impairs hepatic regeneration following partial hepatectomy in mice - Islam, S. M. Touhidul; Palanisamy, Arun P.; Chedister, Gabriel R.; Schmidt, Michael G.; Lewin, David N. B.; Chavin, Kenneth D. (PloS one, 2023)
Partial hepatectomy is a preferred treatment option for many patients with hepatocellular carcinoma however, pre-existing pathological abnormalities originating from hepatic steatosis can alter the decision to perform surgery or postoperative outcomes as a consequence of the impact steatosis has on liver regeneration. The aim of this study was to investigate the role of a saturated or unsaturated high fat diet-mediated steatosis on liver regeneration following partial hepatectomy. Mice were fed a low-fat control diet (CD, 13% fat), lard-based unsaturated (LD, 60% fat) or milk-based saturated high fat diet (MD, 60% fat) for 16 weeks at which time partial hepatectomy (approx. 70% resection) was performed. At days-2 and 7 post hepatectomy, one hour prior to euthanization, mice were injected with 5-bromo-2'-deoxyuridine in order to monitor hepatic regeneration. Serum was collected and assessed for levels of ALT and AST. Resected and regenerated liver tissue were examined for inflammation-indicative markers employing RT-PCR, Western blots, and histological methods. Mice fed LD or MD exhibited higher NAFLD scores, increased expression of inflammatory cytokines, neutrophil infiltration, macrophage accumulation, increased apoptosis, and elevated levels of serum ALT and AST activities, a decrease in the number of BrdU-incorporated-hepatocytes in the regenerated livers compared to the mice fed CD. Mice fed MD showed significantly lower percent of BrdU-incorporated hepatocytes and a higher trend of inflammation compared to the mice fed LD. A diet rich in saturated or unsaturated fat results in NASH with decreased hepatic regeneration however unsaturated fat diet cause lower inflammation and higher regeneration than the saturated fat diet following partial hepatectomy in mice.